KEKERASAN DALAM SENIORITAS DI LINGKUNGAN PENDIDIKAN - Maisandra helena Lohy; Farid Pribadi (Universitas Pendidikan Nasional, 2021)
Violent behavior committed by seniors to juniors in educational circles is still found in many schools and universities. Cases of violence committed by seniors to juniors have generated a lot of attention because cases of violence used by seniors to juniors still exist. Therefore, the purpose of this study is to see what factors are behind violent behavior in seniority in the educational environment. The research method used is descriptive qualitative. As for data collection, namely through literature studies from various journals, books and websites that are in accordance with the topics discussed. The results showed that the factors that cause violent behavior in seniority still exist, namely the lack of social control from the three educational environments, namely family, school, and society. To be able to eliminate violence in seniors, it requires the cooperation of the three educational environments to exercise social control in adolescent behavior in the educational environment. Keyword : violence, seniority, social